PENGARUH TINGKAT SUKU BUNGA DEPOSITO TERHADAP PENINGKATKAN JUMLAH NASBAH PADA PT. BANK RAKYAT INDONESIA (PERSERO) KANTOR CABANG TAKALAR - Ibrahim, Lilly (Perpustakaan dan Penerbitan Unismuh Makassar, 2011)
The research aims to identify and analyze the influence of interest rates on deposits to increase the number of Customers and also estimate the trend of an increasing number of customers of PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Galesong period of next 5 years. The study used secondary data obtained from reports and documents of the company. Analysis of data using simple regression. The research concludes that the deposit interest rate significant positive effect on the increase in the number of customers. Also estimated that for the next 5 years the number of customers will continue to increase with the current interest rate assumptions.